TRANSLYATSIONNYE ISSLEDOVANIYA (TRANSLATION STUDIES): AN OVERVIEW - Farangiz Sultanmuradova Akramovna; Mardiyeva Nozli Alijonovna (European Science Publishing, 2024)
Translation Studies (translyatsionnye issledovaniya) is a dynamic and interdisciplinary field that examines the complexities of translating texts across languages and cultures. It integrates linguistic, cultural, and social perspectives to analyze how translations are produced, received, and their broader implications. The discipline has evolved significantly since its formal emergence in the late 20th century, incorporating various theories and methodologies. Key concepts such as equivalence, Skopos Theory, and cultural considerations are foundational to understanding translation practices. Current trends in Translation Studies highlight the impact of technology, the importance of audiovisual translation, and ethical considerations in the translation process. As globalization continues to shape communication, Translation Studies remains crucial in fostering cross-cultural understanding.
Keywords: Translation Studies, Translyatsionnye issledovaniya, Equivalence, Skopos Theory, Cultural considerations, Machine translation, Audiovisual translation, Translation ethics, Interdisciplinary approaches, Globalization.